Uric Acid and Clinical Outcomes Among Intracerebral Hemorrhage Patients: Results From the China Stroke Center Alliance - Xinmin Liu; Xinmin Liu; Zhentang Cao; Zhentang Cao; Hongqiu Gu; Hongqiu Gu; Hongqiu Gu; Hongqiu Gu; Kaixuan Yang; Kaixuan Yang; Kaixuan Yang; Kaixuan Yang; et al. (Frontiers in Neurology, 2020)
Background and Purpose: The effect of uric acid (UA) levels on severity and prognosis of spontaneous intracerebral hemorrhage (ICH) remains controversial. We aimed to explore the association of admission UA levels with stroke severity and outcomes in ICH patients.Materials and Methods: The patients enrolled in this study were from the China Stroke Center Alliance study (CSCA). Patients were divided into four groups (Q1–Q4) according to the quartiles of UA levels at admission. The primary outcome was in-hospital mortality. The secondary outcomes included stroke severity, in-hospital complications, and discharge disposition. Multivariate logistic regression was adopted to explore the association of UA levels with outcomes after ICH.Results: Patients (84,304) with acute ICH were included in the final analysis; the median (interquartile range) of UA was 277 (210, 354) μmol/L. The four groups were defined as follows: Q1 ≤ 210 μmol/L, 210 μmol/L < Q2 ≤ 277 μmol/L, 277 μmol/L < Q3 ≤ 354 μmol/L, Q4 > 354 μmol/L. There was no significant evidence indicating that UA levels were correlated with the discharge disposition and in-hospital mortality after ICH. However, compared to Q1, the patients with higher UA levels had decreased odds of severe stroke (NIHSS ≥ 16) at admission (OR 0.89, 95% CI 0.86–0.92). An L-shaped association was found between UA and severe stroke. Among in-hospital complications, decrease in pneumonia, poor swallow function, gastrointestinal bleeding, and deep vein thrombosis (DVT) were significantly associated with higher UA levels compared to Q1 (P for trend < 0.0001).Conclusions: UA was a protective factor for stroke severity and in-hospital complications such as pneumonia, poor swallow function, gastrointestinal bleeding, and DVT. However, no significant evidence indicated that UA levels were predictive of the discharge disposition and in-hospital mortality after ICH.